2020
DOI: 10.1186/s40100-019-0138-4
|View full text |Cite
|
Sign up to set email alerts
|

Measuring consumers’ preferences for craft beer attributes through Best-Worst Scaling

Abstract: The current paper investigates consumers' consumption behavior and preferences for craft beer. More specifically, it uncovers consumers' consumption habits and perception about craft beer, as well as their preferences for 13 beer attributes drawn from the literature. The analysis was carried out in Italy by administering a structured questionnaire to 323 consumers. Best-Worst Scaling was used to detect consumers' preferences towards the 13 craft beer attributes. The latter were then ranked on the basis of thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 29 publications
1
27
3
1
Order By: Relevance
“…The authors suggested that microbreweries have an additional edge on the organic beer market, because craft beer consumers are more commonly looking for new flavors and styles of beers to try. In Italy, organic certification was found to be the fourth (on thirteen) most important beer attribute for craft beer drinkers, following taste, fermentation process, and color [114]. Analyzing beer consumer perceptions and preferences along ten years, in a just published systematic review, the authors suggested that consumer perceptions of new styles of beer and speciality beers (such as sustainable or organic beer) require additional attention from scholars and market analysts [115].…”
Section: Quality Aspects and Sustainable Productionmentioning
confidence: 99%
“…The authors suggested that microbreweries have an additional edge on the organic beer market, because craft beer consumers are more commonly looking for new flavors and styles of beers to try. In Italy, organic certification was found to be the fourth (on thirteen) most important beer attribute for craft beer drinkers, following taste, fermentation process, and color [114]. Analyzing beer consumer perceptions and preferences along ten years, in a just published systematic review, the authors suggested that consumer perceptions of new styles of beer and speciality beers (such as sustainable or organic beer) require additional attention from scholars and market analysts [115].…”
Section: Quality Aspects and Sustainable Productionmentioning
confidence: 99%
“…In the same work, the consumer was willing to pay a premium price for the local product. In general, however, the price of this product was found to be a less important attribute for the consumer or less influential than others (Carvalho et al , 2018; Donadini and Porretta, 2017; Lerro et al , 2020; Orth and Lopetcharat, 2006). In other studies, price holds a different degree of importance depending on the geographical context considered (Donadini et al , 2016) and may represent a barrier to purchase CB (Carvalho et al , 2018; Gómez-Corona et al , 2016).…”
Section: Introductionmentioning
confidence: 83%
“…The degree of preference for each attribute of choice was then used in a latent class analysis model to identify homogeneous groups of consumers defined according to the degree of preference towards the set of attributes and socio-demographic characteristics. Other studies in the literature have profiled the typical CB consumer and investigated which attributes they are most interested (Aquilani et al , 2015; Donadini et al , 2016; Donadini and Porretta, 2017; Gómez-Corona et al , 2016; Jaeger et al , 2020), also using the BWS methodology in the Italian context (Lerro et al , 2020); however, to the best of our knowledge, no existing studies have defined different segments of individuals linked to CB consumption.…”
Section: Introductionmentioning
confidence: 99%
“…In the food and beverage industry, consumers perceive the quality by searching for the information of such a product and experiencing the product through its taste and cooking attributes [52], thus, acquiring the information associated with the increasing of consumers' experience. Comparably, in the craft beer sector, consumers are likely to try new craft beers and are "curious to acquire information about [them]" [90] (p. 12). This extent aligns with the findings in the current study that craft beer tourists seek information while they travel to the brewery and participate in the festival.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%